From touristic villages to coastal cities: The costs of the big step in Buenos Aires - Isla, Federico Ignacio (2013)
Coastal villages have grown due the increasing touristic demand of “sun and beach” resorts. This implies more services, more areas for bathing and shadows for tourists. The awkward assessment of touristic beaches and the shortages induced by natural erosion provoked the deterioration of bathing zones. The coastal defence policy and the management of the rain excesses can not reverse this deterioration trend. Storm-water discharges in many places are constructed towards the bathing zones by combined sewer overflows (CSO) systems that increase pollution problems. The decrease of the width of the beach demand interventions. Hard structures (seawalls, groynes) have probed to imply worse impacts; beach nourishment does not solve the problem but permits to rebuilt or modify some beaches under critic stages. The pavements of seaside avenues have been very controversial in some cities subject to storms. Sewage networks were originally oriented to sanitary ponds but odours and pollution of the water table led to reconsider some master plans. At the same time, groundwater is shortening towards the end of the season and new water reserves should be planned. However, federal governments do not envisage the magnitude of future problems, neither the impacts of climatic changes. In this sense, it is necessary to propose alternative coastal-defence policies, to avoid pluvial discharges to bathing areas, to promote aquifer recharges and to reverse the sewage network towards submarine outfalls.